Exposure of wild mammals to glyphosate, AMPA, and glufosinate: a case for “emerging organic contaminants”? - Fritsch, Clémentine; Appenzeller, Brice M. R.; Bertrand, Colette; Coeurdassier, Michael; Driget, Vincent; Hardy, Emilie M; Palazzi, Paul; Schaeffer, Charline; Goydadin, Anne-Claude; Gaba, Sabrina; Bretagnolle, Vincent; Pelosi, Céline (Peer Community Journal, 2025)

(untitled)
Glyphosate (GLY) is the most widely used herbicide worldwide, and its use continues to increase. Accumulating evidence shows that GLY and its metabolite aminomethylphosphonic acid (AMPA) are more persistent and toxic than expected, but little is known about the risks to wildlife. Glufosinate (GLUF) was considered an alternative broad-spectrum herbicide, but its field ecotoxicology has rarely been studied. This study aimed to assess the exposure of free-ranging rodents and shrews from treated (cereals under conventional farming) and nontreated habitats (cereals under organic farming and hedgerows) in France to GLY, AMPA, and GLUF through residue analyses in hair. We investigated the patterns of accumulation according to species, habitat, and treatment intensity at the plot, landscape, or township scale. We showed a generalized exposure of small mammals to GLY, AMPA and GLUF, as they were detected in all of the species, and in 64%, 51% and 44% of the hair samples, respectively. The detection and levels of GLY, AMPA and GLUF were greater in herbivorous and omnivorous voles than in insectivorous shrews and omnivorous wild mice. The three compounds showed comparable ranges of concentrations: 0.018-7.74 pg/mg with an outlier of 522 pg/mg for GLY (median = 2.65 pg/mg), 0.240-33.6 pg/mg for AMPA (median = 1.39 pg/mg), and 1.16-25.5 pg/mg for GLUF (median = 3.51 pg/mg). The frequencies of detection and concentrations did not significantly differ according to the farming practices or proxies of pesticide treatment intensity. The concentrations of GLY were greater in individuals captured in hedgerows than in those captured in cereal fields. On the basis of dose reconstruction approaches and toxicological thresholds from the literature, GLY and GLUF levels may be associated with risk in small mammals and endanger local populations. Our findings raise issues about the omnipresence of GLY, AMPA and GLUF in agricultural landscapes, including in animals from habitats considered refuges, questioning their ecological safety. This work provides new insights into current broad-spectrum herbicide wildlife ecotoxicology that may support decision-making to protect biodiversity.